Calculation the Magnetic Dipole Moments of Some Fluorine Nuclei - Hameed , Ban Sabah (Iraqi Journal of Science, 2022)
The magnetic dipole moments and the root mean square radius have been calculated some the Fluorine (A= 17, 19, 20, 21) isotopes based on the sd-shell model using universal sd-shell interaction A (USDA). All studied isotopes are composed of 16O nucleus that is considered as an inert core and the other valence particles are moving over the sd-shell model space within 1d5/2, 2s1/2 and 1d3/2 orbits. The configuration of mixing shell model with limiting number of orbitals in the model space outside the inert core fail to reproduce the measured magnetic dipole moments. Therefore, and for the purpose of enhancing the calculations, the discarded space has been included the core polarization effect through the effective g-factors. The harmonic oscillator potential is used to generate the single particle matrix elements, where the value of the size parameter b is adjusted to get the experimental root mean square of matter radii for each nucleus calculated.